Education in Post-Conflict Transition The Politicization of Religion in School Textbooks (Palgrave Studies in Religion, Politics, and Policy, 2018)
This book offers vivid insights into policies of religious education in schools since the series of wars in former Yugoslavia in the 1990's. It traces the segregation among members of different ethnic groups in Slovenia, Bosnia-Herzegovina, Croatia, and Serbia, which has never been greater or more systematic. It aims to be a necessary step in understanding the origins of this systematic segregation and how it is reproduced in educational practice, asserting that the politicization of religion in the school textbooks is one of the motors responsible for the ongoing ethnic segregation. It also deals with complex aspects of this issue, such as the general situation of religion in the different countries, the social position of churches, the issues of gender, the reconciliation after the Yugoslav Wars, and the integration of the EU.